2014
DOI: 10.1016/j.eats.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Patellofemoral Ligament Reconstruction Using a Quadriceps Tendon Graft

Abstract: Medial patellar subluxation (MPS) is normally described after a lateral retinacular release. However, isolated MPS in the absence of a previous lateral release does occur. This type of patellar instability is often overlooked, and a high index of suspicion is needed for appropriate diagnosis and treatment. This report describes a technique developed in response to episodes of isolated MPS. The technique uses a partial-thickness graft from the quadriceps tendon to reconstruct the lateral patellofemoral ligament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Medial patellar instability is a recognized problem in patients with anterior knee pain. 12 , 18 – 20 , 22 Most commonly, this has been reported as an iatrogenic consequence of lateral retinacular release, which inadvertently transects the ligamentous structures, at least of the deep layers. 7 , 12 Kaplan 10 first described the anatomic characteristics of the lateral side of the knee and identified a lateral epicondylopatellar ligament running at the level of the deep transverse retinaculum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medial patellar instability is a recognized problem in patients with anterior knee pain. 12 , 18 – 20 , 22 Most commonly, this has been reported as an iatrogenic consequence of lateral retinacular release, which inadvertently transects the ligamentous structures, at least of the deep layers. 7 , 12 Kaplan 10 first described the anatomic characteristics of the lateral side of the knee and identified a lateral epicondylopatellar ligament running at the level of the deep transverse retinaculum.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested imbricating the lateral retinaculum to prevent subluxation, 9 , 15 others advocate soft tissue augmentation using the fascia lata, 1 and some describe a variety of reconstruction methods using autograft and allograft. 3 , 19 , 23 , 24 …”
mentioning
confidence: 99%
“…Many surgical techniques have been described to treat medial patellar instability, using the iliotibial band, patellar tendon, quadriceps tendon with a bone block, or gracilis tendon as a graft. [6][7][8][10][11][12][13] Some individuals have a lateral epicondylopatellar ligament, to a varying degree of frequency, but the superficial oblique and deep transverse retinacular layers are found more consistently. 1 The superficial oblique retinaculum is quite thin.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Reconstructive surgery includes direct ligament repairs 5,9 or reconstructions of the lateral patellofemoral ligament or lateral retinaculum. [6][7][8][10][11][12][13] According to Teitge and Torga Spak, 7 medial patellar instability reappears after the first postoperative year after lateral retinacular repair and imbrication. Given that the literature regarding surgical treatment offers only Level IV or V evidence, the surgical therapeutic approach should be based on the surgeon's common sense, personal experience, and criteria.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Despite the initial study by Hughston and Deese 2 in 1988 and other studies that followed, all of which warned about IMPI, and despite articles written later about avoiding this injury, the problem still exists currently. [8][9][10][11][12][13] Almost all IMPI cases have been caused either by improper patient selection or by overzealous and excessive release of the lateral retinaculum (LR). 1 All too often, the pain and disability from IMPI are much worse than the preoperative symptoms for which the operation was performed, causing serious psychological side effects.…”
mentioning
confidence: 98%